Gender and mobility in the car-dependent urban society of Muscat/ Oman - Didero, Maike; Nebel, Sonja; Pfaffenbach, Carmella (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
This article aims at analysing women’s possibilities in Muscat/Oman to participate in society by being mobile. Taking Muscat’s highly diversified population into account, we included both Omani and Indian family households in a mixedmethods approach using predominantly qualitative interviews. As a result of the urbanisation and modernisation process of the last five decades, the Capital Area of Muscat today forms a linear urban corridor that extends over roughly 80 km. The specific spatial context of a fast growing and widely dispersed urban space, as well as a well-developed road infrastructure combined with a high availability of individual cars are the reasons why individual mobility is predominantly car-based. For the analysis of Omani and Indian women’s mobility the concept of motility was chosen as theoretical framework. Considering the categories access, competence and appropriation, the concept offers a particular enlightening perspective for the case of Muscat, where the socioeconomic position as well as social norms and cultural restrictions play a decisive role in women’s mobility.